Variáveis associadas ao bruxismo em crianças e adolescentes - Gonçalves, Livia Patricia Versiani (2009)
The aim of the study was to assess the variables associated with bruxism and its prevalence in school children and adolescents. A group of 680 school children of both genders aged 4 -16 years old was randomly selected. Data were gathered by clinical exam and questionnaires filled out by guardians. Statistical analyses were performed by Chi-square test, Odds Ratio and SPSS package. Some factors like heredity, respiratory problems, headaches, difficulty with falling asleep, sleep talking and the schoolchild’s disquiet temperament were associated with bruxism occurrence. Bruxism prevalence was 43%. No gender differences were found. It could be concluded that bruxism seems to play a significant role in the schoolchildren’s quality of life, and thus deserves proper identification. However, additional studies should be conducted by multidisciplinary teams involving sleep medicine, dentistry and psychology, in order to best understand bruxism etiology.